Integration of Islamic Values in Sports Extracurricular at Adzkia Integrated Islamic Elementary School - Putra, Ronika; D, Dasrizal; SA, Syaifullah SA (Yayasan Adra Karima Hubbi, 2024)
Background. Islam is a comprehensive religion, meaning that it covers all aspects of human life, but not all of it can be realized by Muslims. As with sports, it is an aspect that is recommended in Islam, because Islam pays great attention to the value of physical health. In line with that, Adzkia Integrated Islamic Elementary School has extracurriculars, namely sports, and all its students adhere to Islam, for that it is necessary to integrate Islamic values into these extracurriculars. Purpose. The research was carried out with a qualitative approach, data was collected by observation techniques, interviews and documentation studies. Data analysis is carried out from data collection, data classification, to drawing conclusions. Method. This research methodology includes literature studies, interviews with tahsin experts, and direct observation of the tahsin teaching process in several Islamic educational institutions. Results. The results of the research are, first, the integration of Islamic values in sports learning, namely teachers ensure that students start sports activities with basmalah, pray and close it with hamdalah. Second, integration is carried out on the material aspect, namely sports materials are not only based on sports materials that are usually done and followed by students, but also introduce to students related to sports that are usual and recommended by the Prophet.. Conclusion. Integration is carried out in the learning aspect, this includes starting from planning, implementation, evaluation, namely teachers carry out the three learning steps in teaching sports by adhering to Islamic ethics and norms.